Sadhana Centre for Management and Leadership Development - Sharma, Rajeev (London : SAGE Publications Ltd, 2017)
The case is about a post graduate institute of management education established in Pune in the year 2004 by Prof. M. S. Pillai. The Institute is visualised as a leadership gurukulam where students become principled, inspiring leaders capable of making contribution to business and spread happiness in the world. None of the programs offered by the institute are affiliated to any university or approved by AICTE. SCMLD is a partner institution of IGNOU so students simultaneously study for MBA from IGNOU. Besides this, several part time courses are conducted in the Institute relating to finance, Systems thinking, Business dynamics and inventory management which students take along with the regular two year programme. Apart from studies, each batch also participates in a 10 day Vipassana meditation course. The case discusses the various initiatives taken by the institution and how they work to shape their students into leaders of tomorrow.
Originally published: Sharma, R. (2013). Sadhana Centre for Management and Leadership Development. RJMC0026. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sadhana Centre for Management and Leadership Development; Management -- Study and teaching -- India -- Pune -- Case studies; Executives -- Training of -- India -- Pune -- Case studies